2018
DOI: 10.1515/rams-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Superplasticity Effect in UFA: History and Development (In Memory of Prof. O.A. Kaibyshev)

Abstract: Prof. O.A. Kaibyshev initiated studies on superplasticity of metals and alloys in Ufa in the 70s-80s of the last century. These studies gave momentum to the development of fundamental and applied studies on superplasticity not only in Russia but in numerous laboratories around the world. This paper highlights the major results of this early work and considers their state-of-the-art and development perspectives for the science and practice of materials superplasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In order to use these techniques for the production of nanostructured samples, it was vitally necessary to confirm the formation of ultrafine-grained microstructure, distinct from the cold-worked one. The orientation imaging characterization techniques were in rudimentary stage at that time (end of 80s of the last century), and an unambiguous confirmation that microstructure of materials processed by ECAP and HPT indeed contains predominantly high angle grain boundaries, delivered the experiments of Valiev et al 9) In this work the authors demonstrated that HPT-processed Al4%Cu0.5%Zr alloy showed superplastic behavior at relatively low for this alloy temperature of 220°C, which could be realized only thanks to the activation of grain boundary sliding and acceleration of grain boundary diffusion. During 10 years after this publication, the scientific research field "Nanomaterials by severe plastic deformation" has been established, which was documented in a fundamental review paper by Valiev et al 16) that has been cited 6200 times by now.…”
mentioning
confidence: 94%
“…In order to use these techniques for the production of nanostructured samples, it was vitally necessary to confirm the formation of ultrafine-grained microstructure, distinct from the cold-worked one. The orientation imaging characterization techniques were in rudimentary stage at that time (end of 80s of the last century), and an unambiguous confirmation that microstructure of materials processed by ECAP and HPT indeed contains predominantly high angle grain boundaries, delivered the experiments of Valiev et al 9) In this work the authors demonstrated that HPT-processed Al4%Cu0.5%Zr alloy showed superplastic behavior at relatively low for this alloy temperature of 220°C, which could be realized only thanks to the activation of grain boundary sliding and acceleration of grain boundary diffusion. During 10 years after this publication, the scientific research field "Nanomaterials by severe plastic deformation" has been established, which was documented in a fundamental review paper by Valiev et al 16) that has been cited 6200 times by now.…”
mentioning
confidence: 94%
“…It is known that the ultra-fine-grained structure in the material has increased physical and mechanical properties, which, in turn, favorably affects the quality of surface layer [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Grain fragmentation and continuous dynamic/post-dynamic recrystallization [7,8] occur at SPD and provide an ultra-fine grain structure consisting of grains with high angle grain boundary misorientation [1,2,4,[6][7][8][9]. As a result, ultra-fine grain aluminum alloys exhibit increased mechanical properties at room temperature [1,4,7,10] and superplasticity at elevated temperatures [11][12][13][14][15]. The main disadvantage of the SPD technique is an increase in the cost of semi-finished products, which can be critical for many applications of aluminum-based alloys.…”
Section: Introductionmentioning
confidence: 99%